An analysis of the performance of selected library schools in Metro Manila based on the Librarians' Licensure Exam (LLE) results - Caldo, Michael L. (2011)
This study aimed to determine whether the factors such as the faculty and students, admission and retention policies of LIS schools, facilities/tools, and curriculum led to the attainment of high performance of non-performance in the librarians' licensure examination of the selected library schools. This study was limited to selected library schools within Metro Manila, namely Philippine Normal University (PNU), Polytechnic University of the Philippines (PUP), University of the Philippines (UP), and University of Santo Tomas (UST).